The development of a STEM-based e-Module to help fifth-grade pupils strengthen their creative thinking skills in the topic of My Blood Circulation - Desak Ketut Rani Astiti Asih; Sunyono Sunyono; Dwi Yulianti; Doni Andra (Lighthouse Publishing, 2021)
Technology and education are now required for the development of 21st century skills. The purpose of this study was to determine 1) the practicality of STEAM-based e-Modules in online learning, 2) the importance of STEAM-based e-Modules in online learning, and 3) the improvement of students' creative thinking skills in fifth grade on the content